Edukasi Jus Melon Sebagai Terapi Non Farmakologi dalam Pengendalian Tekanan Darah - Asrina Pitayanti; Fitria Yuliana (Jurnal Masyarakat Mengabdi Nusantara, 2023)
Hypertension is an increasingly important medical and public health problem. Prevention and management of hypertension is a major public health challenge. Many cardiovascular diseases, cerebrovascular diseases, and hypertension can be prevented by implementing medication through routine control and realizing the importance of a healthy lifestyle. The method used is to provide education and demonstration of non-pharmacological therapy about melon juice. Melon juice therapy can be used as an alternative therapy in lowering blood pressure in hypertensive patients. which is easy and cheap without compromising the benefits of pharmacological drugs applied by medical personnel. The content of melon fruit contains a lot of Potassium which functions to lower blood pressure because it can cause vasodilation, dilate blood vessels, so that blood pressure can decrease. Community service activities are aimed at all residents in order to increase knowledge about non-pharmacological therapies that are relatively safe from side effects.